The Effect of Service Quality on Customer Satisfaction Mediated by Brand Image and Customer Experience of Indibiz in Palu City - Sinta, Tri Ayu; Ponirin, Ponirin; Bachri, Syamsul; Auriza, Mohammad Zeylo (Faculty of Economics dan Business, Atma Jaya Makassar University, 2025)
This study aims to analyze the influence of service quality on customer satisfaction mediated by brand image and customer experience of Indibiz n Palu City. This research employs a quantitative method. The population of the study consists of Indibiz customers at PT Telkom Witel Sulbagteng in Palu City, with a sample size of 105 respondents. Data collection was conducted using a Google Forms questionnaire, and the sampling technique applied was purposive sampling. The data analysis technique used in this study is Partial Least Squares-Structural Equation Modeling (PLS-SEM) with the assistance of SMARTPLS software. The results indicate that the brand image variable does not significantly affect customer satisfaction, while service quality has a significant impact on customer satisfaction, and customer experience also has a significant impact on customer satisfaction. The quality of service mediated by brand image does not have a significant effect on customer satisfaction. The quality of service mediated by customer experience has a significant effect on customer satisfaction.